Fracture initiation and propagation in unidirectional CF composites based on thermoplastic acrylic resins. (15th October 2017) - Pini, T.; Caimmi, F.; Briatico-Vangosa, F.; Frassine, R.; Rink, M.
Highlights: An investigation on the different contributions to fracture toughness of unidirectional composite materials is proposed. The transfer of matrix toughness is related to the size of the process zone proper to the matrix. Fibre bridging contribution is affected by the strength of the interface between matrix and fibre. Abstract: The fracture behaviour of continuous unidirectional carbon fibre composite materials prepared adopting two, one plain and one rubber toughened, thermoplastic acrylic resins as matrices was investigated as a function of temperature and displacement rate. The contributions to fracture toughness of composites given by the matrix and the fibre related mechanisms was analysed by comparing results obtained at crack initiation and during crack propagation stages. It was verified that the transfer of matrix toughness into the composite is only partial when the matrix process zone size is comparable to the interlaminar matrix layer thickness. The effectiveness of fibre bridging mechanism was found to be related to the interfacial strength between the matrix and the fibre.